Individual Clinically Diagnosed with CHARGE Syndrome but with a Mutation in KMT2D, a Gene Associated with Kabuki Syndrome: A Case Report - Sakata, Sonoko; Okada, Satoshi; Aoyama, Kohei; Hara, Keiichi; Tani, Chihiro; Kagawa, Reiko; Utsunomiya-Nakamura, Akari; Miyagawa, Shinichiro; Ogata, Tsutomu; Mizuno, Haruo; Kobayashi, Masao (Frontiers in Genetics, 2017)
We report a Japanese female patient presenting with classic features of CHARGE syndrome, including choanal atresia, growth and development retardation, ear malformations, genital anomalies, multiple endocrine deficiency, and unilateral facial nerve palsy. She was clinically diagnosed with typical CHARGE syndrome, but genetic analysis using the TruSight One Sequence Panel revealed a germline heterozygous mutation in KMT2D with no pathogenic CHD7 alterations associated with CHARGE syndrome. Kabuki syndrome is a rare multisystem disorder characterized by five cardinal manifestations including typical facial features, skeletal anomalies, dermatoglyphic abnormalities, mild to moderate intellectual disability, and postnatal growth deficiency. Germline mutations in KMT2D underlie the molecular pathogenesis of 52%–76% of patients with Kabuki syndrome. This is an instructive case that clearly represents a phenotypic overlap between Kabuki syndrome and CHARGE syndrome. It suggests the importance of considering the possibility of a diagnosis of Kabuki syndrome even if patients present with typical symptoms and meet diagnostic criteria of CHARGE syndrome. The case also emphasizes the impact of non-biased exhaustive genetic analysis by next-generation sequencing in the genetic diagnosis of rare congenital disorders with atypical manifestations.